Pengaruh Subtitusi Agregat Buatan (Beton Daur Ulang) Terhadap Kuat Tekan Beton Normal - Yusra, Andi; Opirina, Lissa (Universitas Teuku Umar, 2019)
The development of building construction has caused the need for construction materials to?increase. Material recycling can be an alternative because it reduces the use of natural materials. Recycled aggregate construction is environmentally friendly construction. This research uses concrete recycle and boiler crust. The recycled concrete used passed the 19.1 mm filter, while the boiler scale was used 15% of the weight of cement by passing the filter No. 200. Variation in the percentage of concrete is recycled to coarse aggregate, 25%, 50%, 75%, 100% and made concrete without recycle as comparable concrete (0%). The strength of concrete is planned to be 30 MPa at 28 days. The weight of concrete without recycle (0%) is 12,430 kg, the use of 25% concrete recycle is 12,419 kg, the use of 50% recycled concrete is 12,245 kg, the use of 75% recycled concrete is 12,131 kg and the use of 100% recycled concrete is 12,106 kg. Test of the average compressive strength of concrete cylinders without the addition of recycled concrete is 30.007 MPa, 25% recycled concrete is 23.213 MPa, 50% recycled concrete is?26.799 MPa, 75% recycled concrete is 16.419 MPa and 100% recycled co ncrete is 20.382?MPa. Overall, it can be seen that the effect of using recycle concrete with the addition of boiler crust to the compressive strength of concrete has decreased to 25%, 50%, 75% and 100%. The decreased in percentage is 22.664%, 10.692%, 45.283% and 32.075%. The results of the study show that the percentage of the optimum aggregates subtitution of recycle in concrete is at?50%, which is equal to 26,799 MPa. Based on SNI 03-6468-2000 concrete with the use of concrete? recycle? with? the addition? of boiler scale at the age of 28? days can? be used? for structural purposes, because the compressive strength is between 12.5 - 40 MPa. The crack pattern that occurs is of two kinds, namely the addition of recycled concrete 0%, 25%, 50% shear and at 75% and 100% in the form of a columnar axis.